Low resistivity conductive paste for built-in heater of aluminum oxide electrostatic chuck and preparation method thereof

CN123033801APending Publication Date: 2026-11-03JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611103811.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

In the existing technology, the resistivity of the conductive paste used for the built-in heater of the alumina electrostatic chuck is difficult to control, and the performance stability is poor, resulting in low heater yield and poor performance consistency.

Method used

A low-resistivity conductive paste formulation is adopted, including tungsten powder, alumina, silicon oxide, magnesium oxide, organic carrier and dispersant. It is prepared by ball milling and vacuum degassing process. The amount of alumina added is limited to achieve precise control of resistivity and is adapted to co-fired matching of alumina ceramic matrix.

Benefits of technology

This achieves precise control of resistivity, improves the conductivity and service life of the heater, reduces interfacial reactions and thermal stress during sintering, enhances the bonding strength between the heater and the substrate, and ensures the consistency of conductivity and the yield of the electrostatic chuck.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a low-resistivity conductive slurry for an embedded heater of an aluminum oxide electrostatic chuck and a preparation method thereof, and belongs to the technical field of electrostatic chuck. The low-resistivity conductive slurry comprises tungsten powder, aluminum oxide, silicon dioxide, magnesium oxide, an organic carrier, ethyl cellulose and a dispersing agent. The preparation method comprises the following steps: S1, inorganic powder ball milling and mixing, tungsten powder, aluminum oxide, silicon dioxide and magnesium oxide are weighed, and inorganic powder uniformly mixed is obtained through ball milling; S2, adding an organic carrier and a dispersing agent, the inorganic powder is added with the organic carrier, ethyl cellulose and the dispersing agent; S3, slurry preparation, the inorganic powder, the organic carrier, ethyl cellulose and the dispersing agent are fully mixed and stirred uniformly, vacuum defoaming is conducted, and conductive slurry is obtained; and S4, calculating resistivity, the conductive slurry is printed on an aluminum oxide green body to form a heating wire, the resistivity is calculated through the following formula after sintering and resistivity testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrostatic chuck technology, and in particular to a low resistivity conductive paste for an alumina electrostatic chuck with an internal heater and its preparation method. Background Technology

[0002] Electrostatic chucks are core components in semiconductor wafer processing equipment. They achieve uniform heating of the wafer through an internal heater to meet the temperature control requirements of processes such as etching and deposition. The performance of the internal heater directly determines the heating uniformity, response speed, and service life of the electrostatic chuck, while the resistivity stability and controllability of the conductive paste used in the heater are key factors affecting the heater's performance.

[0003] Alumina ceramics are the preferred material for electrostatic chuck substrates due to their excellent insulation, thermal conductivity, and chemical stability. However, when fabricating built-in heaters within an alumina matrix, the resistivity of the conductive paste changes significantly with the amount of alumina added: at low alumina content, the paste resistivity fluctuates greatly and lacks stability; at high alumina content, the paste resistivity increases sharply, even exceeding the test range, failing to meet the conductivity requirements of the heater. Currently, the industry lacks conductive paste formulations that can precisely control resistivity and are compatible with the sintering process of alumina electrostatic chucks, resulting in low yield and poor performance consistency of built-in heaters. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a low resistivity conductive paste for an alumina electrostatic chuck built-in heater and its preparation method, thereby solving the problems of difficult resistivity control and poor performance stability of conductive pastes for alumina electrostatic chuck built-in heaters in the prior art, achieving precise control of resistivity, and ensuring the conductivity and long-term stability of the heater.

[0005] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows:

[0006] This invention discloses a low-resistivity conductive paste for an alumina electrostatic chuck with an internal heater, wherein the low-resistivity conductive paste comprises, by mass percentage:

[0007] Tungsten powder: 73.8%–98.8%, including tungsten powder with a particle size of 1μm and tungsten powder with a particle size of 2μm, of which tungsten powder with a particle size of 1μm accounts for 70% and tungsten powder with a particle size of 2μm accounts for 30%;

[0008] Alumina: 2%–25%;

[0009] Silicon dioxide: 0.6%;

[0010] Magnesium oxide: 0.6%.

[0011] Preferably, the low resistivity conductive paste further includes:

[0012] An organic carrier, wherein the mass of the organic carrier is 18% to 25% of the total mass of the powder;

[0013] Ethyl cellulose, wherein the mass of ethyl cellulose is 2% of the total mass of the powder;

[0014] A dispersant, wherein the mass of the dispersant is 1% of the total mass of the powder.

[0015] Preferably, the mass percentage of the alumina is 2% to 10%.

[0016] Another aspect of the present invention discloses a method for preparing a low-resistivity conductive paste for an alumina electrostatic chuck with an internal heater, the method comprising the following steps:

[0017] Step S1: Inorganic powder ball milling and mixing

[0018] Weigh out tungsten powder, alumina, silicon dioxide, and magnesium oxide according to the formula, add them to a ball mill jar, then add zirconia grinding beads, and mill at a speed of 110-120 r / min for 45-50 h to obtain a uniformly mixed inorganic powder.

[0019] Step S2: Add organic carrier and dispersant

[0020] An organic carrier, ethyl cellulose, and a dispersant are added to a uniformly mixed inorganic powder. If the amount of alumina added is less than or equal to 16 wt% and greater than or equal to 2 wt%, the amount of organic carrier added is 18% of the total powder mass. If the amount of alumina added is greater than 16 wt% and less than or equal to 20 wt%, the amount of organic carrier added is greater than 18% and less than or equal to 20% of the total powder mass.

[0021] Step S3: Slurry preparation

[0022] Inorganic powder is thoroughly mixed with organic carrier, ethyl cellulose and dispersant, and then vacuum degassed to obtain conductive slurry for built-in heater of alumina electrostatic chuck.

[0023] Step S4: Calculate resistivity

[0024] The conductive paste described above is screen-printed onto the alumina green blank to form a heating wire. After sintering, the resistance is tested, and the resistivity is calculated using the following formula:

[0025]

[0026] Where ρ is resistivity, R is resistance, L is heating wire length, and S is heating wire cross-sectional area.

[0027] Preferably, in step S2, if the amount of alumina added is 20 wt%, the amount of organic carrier added is 20% of the total mass of the powder; if the amount of alumina added is 25 wt%, the amount of organic carrier added is 25% of the total mass of the powder.

[0028] The above technical solution has the following beneficial effects:

[0029] Precise and controllable resistivity: This invention achieves graded control of slurry resistivity by limiting different ranges of alumina addition. It can stably maintain low resistivity at low addition levels, and linearly adjust resistivity at higher addition levels, adapting to built-in heater designs with different power and heating uniformity requirements.

[0030] Strong process adaptability: The combination of alumina, silicon dioxide and magnesium oxide in the formula can achieve co-firing matching with alumina ceramic matrix, reduce interfacial reaction and thermal stress during sintering, improve the bonding strength between heater and matrix, and avoid defects such as delamination and cracking.

[0031] High performance stability: The resistivity of the slurry fluctuates little under low alumina addition, and the data of parallel samples are consistent, which can ensure the consistency of conductivity of different batches of heaters and improve the yield and service life of electrostatic chucks.

[0032] The preparation process is simple: it adopts conventional ball milling and stirring degassing processes, requires no special equipment, and can be directly adapted to existing electrostatic chuck built-in heater preparation production lines, making it easy to promote and apply industrially. Detailed Implementation

[0033] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] A low-resistivity conductive paste for an alumina electrostatic chuck with an integrated heater, comprising, by weight percentage:

[0035] Tungsten powder: 73.8%–98.8%, including tungsten powder with a particle size of 1μm and tungsten powder with a particle size of 2μm, of which tungsten powder with a particle size of 1μm accounts for 70% and tungsten powder with a particle size of 2μm accounts for 30%;

[0036] Alumina: 2%–25%;

[0037] Silicon dioxide: 0.6%;

[0038] Magnesium oxide: 0.6%;

[0039] Specifically, the low resistivity conductive paste includes powders, namely tungsten powder, alumina, silicon dioxide, and magnesium oxide. The tungsten powder accounts for 73.8 wt% to 98.8 wt% by mass, the alumina accounts for 2 wt% to 25 wt% by mass, the silicon dioxide accounts for 0.6 wt% by mass, and the magnesium oxide accounts for 0.6 wt% by mass, with the total mass percentage of the four being 100 wt%. The tungsten powder includes 1 μm and 2 μm particle size tungsten powder, i.e., the tungsten powder is a mixture of the two, with 1 μm particle size tungsten powder accounting for 70% and 2 μm particle size tungsten powder accounting for 30%.

[0040] Low resistivity conductive pastes also include:

[0041] Organic carrier, the mass of which is 18% to 25% of the total mass of the powder;

[0042] Ethyl cellulose, wherein the mass of ethyl cellulose is 2% of the total mass of the powder;

[0043] Dispersant, the mass of which is 1% of the total mass of the powder;

[0044] Specifically, in addition to the powders mentioned above, the low resistivity conductive paste also includes an organic carrier, ethyl cellulose, and a dispersant. The organic carrier accounts for 18% to 25% of the total powder mass, and can specifically be terpineol. The ethyl cellulose accounts for 2% of the total powder mass and acts as a binder. The dispersant accounts for 1% of the total powder mass and can specifically be BYK-111 (BYK-111 is a solvent-free wetting and dispersing agent produced by BYK Chemicals in Germany). The total powder mass is the sum of the masses of tungsten powder, alumina, silica, and magnesium oxide.

[0045] When the amount of alumina added is 2% to 4%, the slurry is in a low resistivity plateau region, and the resistivity change trend is not obvious, which meets the low resistance conductivity requirements of the heater.

[0046] When the alumina addition amount is 4wt% to 10wt%, the resistivity increases slowly with increasing addition amount, starting from 1.06 × 10⁻⁶. -5 Ω•cm increased to 1.32×10 -5 Ω•cm, the resistivity can be linearly controlled by fine-tuning the amount added;

[0047] When the alumina addition is 10wt%–20wt%, the resistivity enters a rapid increase region, starting from 1.32 × 10⁻⁶. -5 Ω•cm increased to 4.46×10 -5 Ω•cm, the amount added should be controlled to be less than or equal to 20wt% according to process requirements to avoid resistivity exceeding the usage range;

[0048] When the amount of alumina added is greater than or equal to 25 wt%, the resistivity of the slurry exceeds the conventional test range and cannot meet the conductivity requirements. Therefore, the preferred amount added in this invention is less than or equal to 20 wt%.

[0049] In some embodiments, the mass percentage of alumina is 2% to 10%; specifically, the mass percentage of alumina is in the range of 2 wt% to 10 wt%, at which point the volume resistivity of the slurry is stably controlled at 1.03 × 10⁻⁶. -5 Ω•cm~1.21×10 -5 Within the Ω•cm range, the sintering compatibility between the slurry and the matrix and the conductivity can be balanced. At this point, the resistivity shows a controllable and slow upward trend with the amount added.

[0050] A method for preparing a low-resistivity conductive paste for an alumina electrostatic chuck with an internal heater includes the following steps:

[0051] Step S1: Inorganic powder ball milling and mixing

[0052] Weigh out tungsten powder, alumina, silicon dioxide, and magnesium oxide according to the formula, add them to a ball mill jar, then add zirconia grinding balls, and mill at a speed of 110-120 r / min for 45-50 h to obtain a uniformly mixed inorganic powder; specifically, add tungsten powder, alumina, silicon dioxide, and magnesium oxide to a ball mill jar, then add zirconia grinding balls for ball milling, wherein the milling speed is 110 r / min, 120 r / min, or 115 r / min, and the milling time is 45 h, 50 h, or 47 h, and a uniformly mixed inorganic powder is obtained after ball milling;

[0053] Step S2: Add organic carrier and dispersant

[0054] An organic carrier, ethyl cellulose, and a dispersant are added to a uniformly mixed inorganic powder. If the amount of alumina added is less than or equal to 16 wt% and greater than or equal to 2 wt%, the amount of organic carrier added is 18% of the total powder mass. If the amount of alumina added is greater than 16 wt% and less than or equal to 20 wt%, the amount of organic carrier added is greater than 18% and less than or equal to 20% of the total powder mass.

[0055] Specifically, an organic carrier, ethyl cellulose, and a dispersant are added to a uniformly mixed inorganic powder. The amount of organic carrier added is determined based on the amount of alumina powder added. If the amount of alumina added is less than or equal to 16 wt% and greater than or equal to 2 wt%, the amount of organic carrier added is 18% of the total powder mass. If the amount of alumina added is greater than 16 wt% and less than or equal to 20 wt%, the amount of organic carrier added is greater than 18% and less than or equal to 20% of the total powder mass. If the amount of alumina added is greater than 20 wt% and less than or equal to 25 wt%, the amount of organic carrier added is greater than 20% and less than or equal to 25% of the total powder mass. The amount of ethyl cellulose added is 2% of the total powder mass, and the amount of dispersant added is 1% of the total powder mass.

[0056] Step S3: Slurry preparation

[0057] Inorganic powder is thoroughly mixed with organic carrier and dispersant, and then vacuum degassed to obtain conductive slurry for built-in heater of alumina electrostatic chuck.

[0058] Step S4: Calculate resistivity

[0059] The conductive paste described above is screen-printed onto the alumina green blank to form a heating wire. After sintering, the resistance is tested, and the resistivity is calculated using the following formula:

[0060]

[0061] Where ρ is resistivity, R is resistance, L is heating wire length, and S is heating wire cross-sectional area.

[0062] In some embodiments, in step S2, if the amount of alumina added is 20 wt%, the amount of organic carrier added is 20% of the total powder mass; if the amount of alumina added is 25 wt%, the amount of organic carrier added is 25% of the total powder mass.

[0063] This invention achieves graded control of slurry resistivity by limiting different ranges of alumina addition. Low resistivity can be stably maintained at low addition levels, while resistivity can be linearly adjusted at higher addition levels, adapting to built-in heater designs with different power and heating uniformity requirements.

[0064] Strong process adaptability: The combination of alumina, silicon dioxide and magnesium oxide in the formula can achieve co-firing matching with alumina ceramic matrix, reduce interfacial reaction and thermal stress during sintering, improve the bonding strength between heater and matrix, and avoid defects such as delamination and cracking.

[0065] High performance stability: The resistivity of the slurry fluctuates little under low alumina addition, and the data of parallel samples are consistent, which can ensure the consistency of conductivity of different batches of heaters and improve the yield and service life of electrostatic chucks.

[0066] The preparation process is simple: it adopts conventional ball milling and stirring degassing processes, requires no special equipment, and can be directly adapted to existing electrostatic chuck built-in heater preparation production lines, making it easy to promote and apply industrially.

[0067] The resistance and resistivity of heating wires prepared with different amounts of alumina are shown in Table 1 below:

[0068] Table 1:

[0069]

[0070] As shown in Table 1, when the amount of alumina added is between 2 wt% and 10 wt%, the resistivity increases slowly with increasing addition amount, starting from 1.03 × 10⁻⁶. -5 Ω•cm increased to 1.32×10 -5 Ω•cm, the resistivity can be linearly controlled by fine-tuning the amount added.

[0071] Example 1

[0072] Preparation of a conductive paste with controllable resistivity:

[0073] Raw material composition (mass percentage): 88.8 wt% tungsten powder (70% tungsten powder with a particle size of 1 μm and 30% tungsten powder with a particle size of 2 μm), 10 wt% alumina, 0.6 wt% silica, and 0.6 wt% magnesium oxide; the amount of organic carrier added is 18% of the total powder mass, the amount of ethyl cellulose added is 2% of the total powder mass, and the amount of dispersant added is 1% of the total powder mass.

[0074] Preparation method: Weigh the powder according to the formula, add 200g of ball milling beads, and ball mill at 115r / min for 48h; add organic carrier, ethyl cellulose and dispersant, stir evenly and then degas under vacuum, and print the paste on the alumina green blank by screen printing to form a heating wire. After sintering, test the resistance and calculate the resistivity by formula.

[0075] Example 2: High resistivity critical region conductive paste (alumina addition 20%)

[0076] Preparation of a conductive paste with controllable resistivity:

[0077] Raw material composition (mass percentage): conductive phase powder 78.8 wt% (70% tungsten powder with a particle size of 1 μm and 30% tungsten powder with a particle size of 2 μm), alumina 20 wt%, silicon dioxide 0.6 wt%, magnesium oxide 0.6 wt%; the amount of organic carrier added is 20% of the total powder mass, the amount of ethyl cellulose added is 2% of the total powder mass, and the amount of dispersant (BYK-111) added is 1% of the total powder mass.

[0078] Preparation method: Same as in Example 1;

[0079] Performance testing: The volume resistivity of the slurry is 4.46 × 10⁻⁶. -5 Ω•cm is at the critical value of the rapid rise zone. At this point, it is necessary to control the amount added to prevent it from increasing further, so as to avoid the resistivity from exceeding the usage range.

[0080] Comparative Example 1

[0081] Preparation of a conductive paste with controllable resistivity:

[0082] Raw material composition: Alumina addition amount 25wt%, the rest is the same as in Example 1;

[0083] Performance testing: The resistivity of the slurry exceeds the standard test range and cannot meet the conductivity requirements, proving that an addition amount of 25% or more is not suitable for conductive slurries with built-in heaters.

[0084] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A low-resistivity conductive paste for an alumina electrostatic chuck with an internal heater, characterized in that, The low resistivity conductive paste comprises, by weight percentage: Tungsten powder: 73.8%–98.8%, including tungsten powder with a particle size of 1μm and tungsten powder with a particle size of 2μm, of which tungsten powder with a particle size of 1μm accounts for 70% and tungsten powder with a particle size of 2μm accounts for 30%; Alumina: 2%–25%; Silicon dioxide: 0.6%; Magnesium oxide: 0.6%.

2. The low resistivity conductive paste for an alumina electrostatic chuck with an internal heater according to claim 1, characterized in that, The low resistivity conductive paste also includes: An organic carrier, wherein the mass of the organic carrier is 18% to 25% of the total mass of the powder; Ethyl cellulose, wherein the mass of ethyl cellulose is 2% of the total mass of the powder; A dispersant, wherein the mass of the dispersant is 1% of the total mass of the powder.

3. The low resistivity conductive paste for an alumina electrostatic chuck with an internal heater according to claim 1, characterized in that, The mass percentage of the alumina is 2% to 10%.

4. A method for preparing a low-resistivity conductive paste for an alumina electrostatic chuck built-in heater as described in any one of claims 1-2, characterized in that, The preparation method includes the following steps: Step S1: Inorganic powder ball milling and mixing Weigh out tungsten powder, alumina, silicon dioxide, and magnesium oxide according to the formula, add them to a ball mill jar, then add zirconia grinding beads, and mill at a speed of 110-120 r / min for 45-50 h to obtain a uniformly mixed inorganic powder. Step S2: Add organic carrier and dispersant An organic carrier, ethyl cellulose, and a dispersant are added to a uniformly mixed inorganic powder. If the amount of alumina added is less than or equal to 16 wt% and greater than or equal to 2 wt%, the amount of organic carrier added is 18% of the total powder mass. If the amount of alumina added is greater than 16 wt% and less than or equal to 20 wt%, the amount of organic carrier added is greater than 18% and less than or equal to 20% of the total powder mass. Step S3: Slurry preparation Inorganic powder is thoroughly mixed with organic carrier, ethyl cellulose and dispersant, and then vacuum degassed to obtain conductive slurry for built-in heater of alumina electrostatic chuck. Step S4: Calculate resistivity The conductive paste described above is screen-printed onto the alumina green blank to form a heating wire. After sintering, the resistance is tested, and the resistivity is calculated using the following formula: Where ρ is resistivity, R is resistance, L is heating wire length, and S is heating wire cross-sectional area.

5. The method for preparing the low resistivity conductive paste for the built-in heater of the alumina electrostatic chuck according to claim 4, characterized in that, In step S2, if the amount of alumina added is 20 wt%, the amount of organic carrier added is 20% of the total mass of the powder; if the amount of alumina added is 25 wt%, the amount of organic carrier added is 25% of the total mass of the powder.